제습제와 채널이 제습로터 성능에 미치는 영향 - 정재동; 이대영; 윤석만 (대한설비공학회, 2007)
The desiccant rotor is the most essential component of desiccant cooling system, but one of its drawbacks to spread out is rotor size. To reduce the size of rotor the analysis of rotor performance is crucial. Systematic examination on the effect of desiccant and channel geometrics has been conducted based on the numerical program previously developed. Considered parameters related to channel geometrics are channel shape and cross section area of channel, and parameters related to desiccant are mass fraction, heat capacity, density, maximum water uptake and separation factor of isotherm. Considerable reduction of rotor size is expected by adjusting the parameters.